The Development of Web-Based Geographic Information System for Leprosy Prevention Program in Jember Regency in 2019 - Yudhi Tri Gunawan; Sri Hernawati; Saiful Bukhori (Humanistic Network for Science and Technology (HNST), 2021)
Leprosy is a chronic granulomatous infectious disease caused by the obligate intracellular organism Mycobacterium leprae. It affects mainly the skin and peripheral nerves. Moreover, it can cause severe physical disabilities and abnormalities. Jember Regency has not reached the Leprosy Elimination status until 2019 because the prevalence rate was still above 1 per 10,000 population. Based on data from the District Health Office of Jember, the findings of leprosy cases in Jember Regency fluctuate every year. The research objective in developing a web-based Geographic Information System was to display information on visualization of leprosy cases; therefore, it could become the basis for policy considerations for leprosy prevention efforts in Jember Regency. The research method was a Rapid Application Development (RAD) system. The research data and information were collected through interviews and document review. This system was designed for helping users have more accessible access to input data and automation of processing into information for users and visitors. Epidemiological interpretation of leprosy on a visual map could determine the magnitude of the case problem and Primary Health Care’s reach in leprosy prevention.Keywords: geographic information system (GIS); elimination; leprosy